2021
DOI: 10.1590/1980-0037.2021v23e75863
|View full text |Cite
|
Sign up to set email alerts
|

Variations of workload and well-being measures across a professional basketball season

Abstract: The aims of this study were: (i) to describe weekly variations of acute load (AL), acute:chronic workload ratio, delayed onset muscle soreness (DOMS), and fatigue; (ii) to analyze variations of weekly workload and well-being in three periods of the season (P1, P2, and P3); and (iii) to analyze the relationships between workload and well-being measures. Fifteen professional basketball players from a first-league European club were monitored throughout the season using the CR-10 Borg scale and the Hooper questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…None of the two studies [34,36] analyzed U14 soccer players, suggesting more studies with similar designs and larger sample sizes. Even in professional basketball players, higher values of DOMS and fatigue were found to be related to AW and ACWLR [37], but this was not shown in this study. Therefore, other contextual factors may influence the well-being of elite U14 soccer players (e.g., external load, nutritional intake, psychological and social aspects).…”
Section: Discussioncontrasting
confidence: 89%
“…None of the two studies [34,36] analyzed U14 soccer players, suggesting more studies with similar designs and larger sample sizes. Even in professional basketball players, higher values of DOMS and fatigue were found to be related to AW and ACWLR [37], but this was not shown in this study. Therefore, other contextual factors may influence the well-being of elite U14 soccer players (e.g., external load, nutritional intake, psychological and social aspects).…”
Section: Discussioncontrasting
confidence: 89%
“…In the same line, Nobari et al showed that high volume of sprinting during high intensity weeks was associated with non-contact injury occurrence [53]. Moreover, Ferreira et al [42] found that well-being measures such as higher DOMS and fatigue values were associated with acute load and ACWR values in professional basketball players. Thus, they reported that significant decreases were determined in acute load from pre-season to the in-season, while DOMS and fatigue levels were high.…”
Section: Discussionmentioning
confidence: 94%
“…The ACWR can be beneficial in explaining the risks associated with the injury rate of athletes such as sudden increases in intensity or critical intensity reductions and describing weekly changes (to check advancement or over intensity strategies) [42]. Starters exhibited significantly greater values for ACWR of DOMS than non-starters in M2, M7, M9, and also ACWR of fatigue values were found to be significantly greater in starters than non-starters in M7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have frequently shown that internal or external workload indices [ 43 ]. In addition, the Hooper Index parameters were found to be higher during the pre-season period compared to other periods of the season [ 44 , 45 ]. The increase in training load parameters in the pre-season is usually due to the progressive overload principle of training, to prepare the players to meet the physical demands of the upcoming season [ 39 ].…”
Section: Discussionmentioning
confidence: 99%